Herpes Zoster Pada Laki-Laki Usia 60 Tahun - Adilla Afra Amri; M Mimbar Topik (Lembaga Pengembangan Kinerja Dosen, 2023)
Esophageal foreign bodies are sharp or blunt objects or food that gets stuck and wedged in the esophagus due to being swallowed either intentionally or accidentally. A 53-year-old male patient came with complaints of swallowing pain since 4 days ago, the pain is felt all the time and gets worse when swallowing. Initially the pain was felt above the throat but after trying alternative traditional methods to remove the bones, the pain was felt to move to the area below the throat. Os has a history of ingesting tuna bones 4 days ago before entering the hospital. Esophagoscopy was performed and obtained fishbone in the esophageal area.